Penilaian Kemampuan Kognitif dan Psikomotor Perawat Panti Werdha dalam Penilaian Inkontinensia Urin pada Lansia di Panti Surya Surabaya - Abigael Grace Prasetiani; Ika Yuni Widyawati; Sukma Randani Ismono (Universitas Airlangga, 2019)
Introduction: Basic assessment in elderly with urinary or bladder dysfunction need holistically and comprehensive approach. A nurse should be given special training to assess and manage urinary incontinence, because it’s complexity especially in elderly. The aimed of this study was to analyze correlation between cognitive and psychomotor nurses ability in assessing urinary incontinence using the Continence Guidelines Assessment and Provision of Containment Products for Community Nursing (CGA-PCP) in elderly.Method: Descriptive analysis was used in this study. The number of samples were 10 nurses and 20 elderly that choosed randomly to assess urinary incontinence using CGA-PCP. Data were analyze using Spearman Rho with significant value p<0.05.Result: The results showed that the value p=0.00, then the value p=0.00<0.05 meaning there were correlation between cognitive and psychomotor nurse ability.Discussion: The conclusions of this study were correlated between cognitive and psychomotor nurses ability. Hopefully nurses can identify the types of urinary incontinence to determine conservative management of urinary incontinence in elderly